ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELANJA DI E-COMMERCE PADA MAHASISWA PENDIDIKAN EKONOMI ANGKATAN 2021 - Afrisa, Sena; Muazza, Muazza; Yaldi, Destri (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
This study was motivated by the increasing popularity of online shopping among students, particularly on e-commerce platforms. The purpose of this study was to identify the factors that influence the interest in e-commerce shopping among 2021 Economics Education students. This study employed a quantitative method with an ex post facto approach. The research population consisted of 100 students majoring in Economics Education in the 2021 cohort, who were also used as samples using saturated sampling techniques. Data were collected using questionnaires dan analysed using validity dan reliability tests as well as factor analysis with the help of SPSS version 27. The results showed that there were six factors influencing students' interest in shopping on e-commerce, namely security, convenience, ease, price, experience, dan product quality. The most dominant factor influencing students' interest in shopping was customer satisfaction, with a contribution of 59.789%. Meanwhile, brand credibility also contributed to students' interest in shopping, with a value of 11.159%. It can be concluded that student shopping interest in e-commerce is influenced by both economic dan non-economic factors, with customer satisfaction being the main factor. Therefore, e-commerce players need to improve service quality, transaction security, dan user convenience in order to maintain consumer shopping interest. The limitations of this study lie in its scope as well as the research variables, which only examine customer satisfaction dan brand credibility.